Heritage building preservation through building information modelling: reviving cultural values through level of development exploration - Ali, Maisarah; Mohd Ismail, Kamsiah; Hashim, Khairusy Syakirin Has-Yun; Mohamad Suhaimi, Mohamad Saifulnizam; Mustafa, Muhammad Hadi (2018)
Despite the rich and diverse heritage buildings in Malaysia, they suffer from many problems and threats. Many heritage buildings are deteriorating, and this threatens the country’s cultural values. The deterioration of built heritage is a result of the poor inheritance of its related documentation and need to be addressed. Thus, this study brought forward the concept of preservation using Building Information Modelling (BIM). Exploring the potential of BIM as a preservation tool in reviving local cultural values might help to balance the problem of poor inheritance or inconsistency in managing historic and documentation maintenance. The aim of this paper is to study the relationship between levels of development (LOD) and usage of BIM in heritage building preservation. This study employs exploratory research using content analysis. The result of the study found that the availability of as-built details (LOD 500) of the building would be the crucial dataset needed for BIM to function in heritage building as H-BIM. This paper suggests on techniques available for constructing Level of Development (LOD) needed for H-BIM.